Exploring Patanjali Yoga Sutra from the Communication Perspective - Shukla, Aditya Kumar; Adhikary, Nirmala Mani; Singh, Sukhnandan (Bodhi: An Interdisciplinary Journal, 2024)
Patanjali Yoga is the primary school of thought in the Indian philosophical system known as Shad-darshan. It is known for its scientific and practical approach. Patanjali Yoga, as such, does not deal with communication directly. Though it is a spiritual treatise, it addresses the behavioral aspects of the Yoga aspirant, thus holding profound ethical significance from the perspective of interpersonal communication. The Patanjali Yoga Sutra provides deep insight into the communication process at different levels, leading the aspirant to the ultimate state of consciousness, or Self-realization, liberation, peace, freedom, and bliss. This research aims to describe the intrapersonal, interpersonal, and transpersonal aspects of communication, as well as obstructions and aiding factors, as envisioned in the Patanjali Yoga Sutra.